SITUASI PNEUMONIA PADA BALITA DI KABUPATEN WAJO PROVINSI SULAWESI SELATAN: Indonesia - Sahruni; Andi Sabriaksa; Abdul Kadir (Andragogi Kesehatan, 2024)
Pneumonia is an infectious disease characterized by inflammation of one or both of the lungs which can be caused by viruses, fungi, bacteria, causing reduced ability of the air sacs to absorb oxygen. The aim of the study was to describe the cases of pneumonia under five in Wajo Regency. The research method applied was a descriptive epidemiological design using secondary data. The study population was pneumonia cases in toddlers who were registered at the Wajo District Health Office in 2018 - 2019. The results of the study found that the highest cases of pneumonia in boys were 58% in 2018 as well as in 2019 at 64.28%. The highest age group at 1 - <5 years was 60.29% and in 2019 the highest was in the 1 - <5 years age group at 65.47%. The number of cases based on the highest month was in March both in 2018 and 2019 amounting to 14.14% and 16.67%. The highest spread of pneumonia cases was in the Belawa Puskesmas working area at 15.6% in 2018and in 2019 Puskesmas Pitumpanua at 24.4%. The conclusion of pneumonia cases in children under five in Wajo District has decreased from 205 cases in 2018 to 168 cases in 2019, the highest cases in the working area of ​​Puskesmas Belawa in 2018 and Puskesmas Pitumpanua in 2019. Keywords: toddlers, wajo district, pneumonia